Influence of Packaged Transportation on Shelf Life and Quality of Banana (Musa spp) Fruits - Mebratie, Mulualem Azene; Woldetsadik, Kebede; Ayalew, Amare; Haji, Jema (Journal of Postharvest Technology, 2016)
The influence of packaged transportation on shelf life and quality of banana  (Musa spp cv. Dwarf Cavendish) fruit was evaluated. Bananas were  transported from production area to Haramaya University (about 900 km) after  packed with wooden crate, plastic crate, wooden crate with low density  polyethylene plastic (LDPE), plastic crate with LDPE, fiberboard box with  LDPE, fiberboard box with LDPE and chemical treatment, and with banana  leaf. Plastic crate was better than wooden crate and banana leaf packages in  maintaining fruit quality and extending shelf life; however, packing in boxes  with plastic liners was better than those without liners. Packing chemical  treated bananas in fiberboard box with plastic liners resulted in longer shelf life  (13 days) and higher percentage of marketability with conservation of other  physico-chemical parameters. This packaging can thus be used to transport and  store bananas for more than 24 days with about 90% marketability while other  boxes with plastic liner can be used for relatively shorter period of about 8  days. As far as artificial ripening is practiced, plastic crate is also good  alternative to pack and transport bananas for local market. However, further  study, including cost benefit analysis with bulk transportation is suggested.
Keywords: Banana; Packaging; Quality; Shelf life; Transportation